SAT0441 BODY COMPOSITION AND FAT DISTRIBUTION IN PATIENTS WITH PSORIASIS OR PSORIATIC ARTHRITIS. (2nd June 2020) - Toussirot, E.; Aubin, F.; Desmarets, M.; Wendling, D.; Auge, B.; Gillard, J.; Messica, O.; Guillot, X.; Laheurte, C.; Monnet, E.; Dumoulin, G.
Abstract : Background: Obesity is a leading comorbidity in both psoriasis (Pso) and psoriatic arthritis (PsA) and is associated with common metabolic complications and increased cardiovascular (CV) risk. Obesity is also a risk factor for the onset of these diseases. Body composition and fat distribution have been rarely evaluated in Pso and PsA. Objectives: In this study, we aimed to characterize the fat mass distribution in patients with Pso or PsA compared to a control group, with a special emphasis on the android/visceral region. Methods: case-control study (NCT02849795 ). Patients with Pso (plaque psoriasis) or PsA (CASPAR criteria) were evaluated. Each patient was paired to a control subject, recruited in the same outpatient population, and matched for sex, age and body mass index (BMI) category. Clinical assessment included BMI, anthropometric measurements (waist circumference, waist /hip ratio), disease activity (PASI for Pso, CPDAI for PsA) and the SCORE CV risk score. Laboratory parameters of inflammation (ESR, CRP, IL-6), lipid parameters (total cholesterol, LDL and HDL cholesterol, triglycerides), metabolic parameters (glycemia, insulin, HOMA), serum adipokines (total and high molecular weight [HMW] adiponectin, leptin, resistin and retinol binding protein 4 [RBP4]) were measured. Body composition (lean mass, fat mass) and fat distribution (android/gynoid regions and visceral fat) were evaluated (DEXA, Lunar GE, CoreScan). Our primary criteria was the fat mass in the android/visceral region. Comparisons between patients and controls were performed with paired t tests, between all groups with ANCOVA (adjusted for age, sex, and BMI category) and Tukey post-hoc tests. Pearson correlations between CV risk and fat mass were calculated within groups. Results: 52 patients with Pso and 52 patients with PsA and their respective paired-control were evaluated. Total fat mass was increased in Pso but not in PsA. Android fat and visceral fat were found higher in Pso (p<0.05) while the fat mass measurements did not differ between the patients with PsA and their controls. Waist circumference was higher in patients with Pso compared to their controls. Leptin, leptin/fat mass ratio, and total adiponectin were elevated in PsA while only the HMW/total adiponectin ratio was decreased in Pso. Insulin levels and HOMA were increased in both Pso and PsA groups. Finally, RBP4 was higher in both Pso and PsA patients compared to their respective controls. In patients with Pso, android and visceral fat were correlated with SCORE (r=0.3, p=0.02 and r= 0.6, p < 0.0001 respectively). In ANCOVA analysis, visceral fat was higher in Pso patients (p=0.0029), with a trend toward higher android fat (p=0.055), compared to PsA patients. Conclusion: visceral fat is increased in patients with Pso but not in PsA. In parallel, both groups showed an elevation of circulating RBP4. Patients with Pso and PsA were also characterized by metabolic disturbances as showed by the increase in HOMA, and specific adipokine changes. In the Pso group, visceral fat is associated with CV risk evaluated by SCORE. Weight control and reduction of fat mass, especially visceral fat mass, may thus be an important concern in patients with Pso and appears less relevant in PsA. Disclosure of Interests: None declared